Mechanistic Insights into Oxidative Damage and Chronic Inflammation - Dr.Zarafshan Gul; Dr.Jabir Khan; Dr. Zaid Ihsan; Dr. Aiman Khan, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Smokeless tobacco (ST) products play leading roles in the aetiology of oral cancer in human beings following mechanisms that include oxidative stress, chronic inflammation and microbial dysbiosis within the oral cavity. This review summarizes the existing studies in terms of how carcinogens contained in ST, which include tobacco-specific nitrosamines (TSNAs) andpolycyclic aromatic hydrocarbons (PAHs), cause production of reactive oxygen species (ROS), damaged DNA, and genome instability. Moreover, the exposure to ST induces prolonged stimulation of proinflammatory cytokines and transcription factors that promotes a pro-tumorigenic microenvironment. Another question the review deals with is the changes in the oral microbiome due to the ST use which creates conditions where pathogenic species develop and play the role in the carcinogenesis. The insight of these complex molecular pathways is important to devise specific therapy plans, such as administration of antioxidants and antiinflammatory compounds, to reduce the risk of oral cancer associated with ST.